Initial dosing of intermittent vancomycin in adults: estimation of dosing interval in relation to dose and renal function - Šíma, Martin; Hartinger, Jan; Grus, Tomáš; Slanař, Ondřej (European journal of hospital pharmacy, 2021)
OBJECTIVES: Due to the high interindividual variability in vancomycin pharmacokinetics, optimisation of its dosing is still challenging. This study aimed to explore vancomycin pharmacokinetics in adult patients and to propose an easy applicable dosing nomogram for initial treatment. METHODS: Vancomycin pharmacokinetics was calculated in a two-compartmental model based on therapeutic drug monitoring data. A linear regression model was used to explore the relationship between vancomycin elimination half-life and glomerular filtration rate estimated according the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula. RESULTS: In the whole study population (n=66), vancomycin volume of distribution, clearance and half-life median (IQR) values were 0.69 (0.58-0.87) L/kg, 0.031 (0.022-0.050) L/h/kg and 14.4 (9.5-25.2) hours, respectively. Vancomycin half-life was associated with glomerular filtration rate (r2=0.4126, p<0.0001) according to the formula: t1/2 (h) = -0.247×eGFRCKD-EPI (mL/min/1.73 m2)+32.89. This relationship was used to construct a dosing nomogram. CONCLUSIONS: We propose an easy-to-use dosing nomogram for vancomycin therapy initiation that allows individualisation of the dosing interval with respect to the administered dose size and functional renal status.
Keywords: CKD-EPI; Drug Monitoring; Glomerular Filtration Rate; antibakteriální látky; dosing nomogram; Adult; Kidney; dospělí; Vancomycin; glomerular filtration; lidé; Anti-Bacterial Agents; pharmacokinetics; Humans; ledviny; monitorování léčiv; therapeutic drug monitoring; vankomycin; hodnoty glomerulární filtrace; vancomycin